Instrument testing for descriptive text writing on the cosmological axis of Yogyakarta and its historical landmarks for BIPA level 5 - Nova Diadara; Rosita Rahma; Yulianeta Yulianeta; Halimah Halimah (Universitas Dian Nuswantoro, 2026)
BIPA learning is inseparable from cultural learning. This study aims to validate and test a writing instrument for descriptive texts containing the tourism of the Cosmological Axis of Yogyakarta for BIPA Level 5. The novelty of this research lies in the integration of the historical-cultural values of the Cosmological Axis into an authentic portfolio writing-based assessment for foreign learners. This study uses the ADDIE Research and Development (R&D) model with an exploratory descriptive approach. The research subjects consisted of three expert validators, two academics who are competent in the fields of Indonesian language teaching, assessment, or BIPA curriculum, and one BIPA practitioner who is experienced in managing productive learning. In addition, two BIPA Level 5 students were involved as limited trial participants. The validation analysis results indicate that the developed instrument consistently falls into the feasible to highly feasible categories across all expert validators. Furthermore, the limited trial results prove that this instrument is effective; the learners were able to follow the portfolio writing process well and correctly understand the cultural concepts of the Cosmological Axis of Yogyakarta. Theoretically, this research contributes to enriching the literature on the development of BIPA assessments integrated with local culture (the Cosmological Axis of Yogyakarta) and digital media (Notion). Practically, this instrument serves as a valid and comprehensive evaluation tool for teachers, and can be utilized as an independent learning resource for BIPA Level 5 learners.